Allergic contact dermatitis due to nickel in household detergent - Dewi Utami Putri; Irma Damayanti Roesyanto-Mahadi (JDVI (Journal of General Procedural Dermatology & Venereology Indonesia), 2017)
Allergic contact dermatitis (ACD) is a cutaneous inflammatory reaction caused by contact with specific exogenous allergen to which a person has developed allergic sensitization. Nickel was reported as one of the most common causes of ACD worldwide, particularly affecting females. It is associated with a variety of nickel-containing products, from jewelry to detergent.